Roles for endothelial cell and macrophage Gch1 and tetrahydrobiopterin in atherosclerosis progression. Issue 10 (27th March 2018) - Douglas, Gillian; Hale, Ashley B; Patel, Jyoti; Chuaiphichai, Surawee; Al Haj Zen, Ayman; Rashbrook, Victoria S; Trelfa, Lucy; Crabtree, Mark J; McNeill, Eileen; Channon, Keith M
Abstract: Aims: GTP cyclohydrolase I catalyses the first and rate-limiting reaction in the synthesis of tetrahydrobiopterin (BH4), an essential cofactor for nitric oxide synthases (NOS). Both eNOS and iNOS have been implicated in the progression of atherosclerosis, with opposing effects in eNOS and iNOS knockout mice. However, the pathophysiologic requirement for BH4 in regulating both eNOS and iNOS function, and the effects of loss of BH4 on the progression of atherosclerosis remains unknown. Methods and results: Hyperlipidemic mice deficient in Gch1 in endothelial cells and leucocytes were generated by crossing Gch1 fl/fl Tie2cre mice with ApoE –/– mice. Deficiency of Gch1 and BH4 in endothelial cells and myeloid cells was associated with mildly increased blood pressure. High fat feeding for 6 weeks in Gch1 fl/fl Tie2CreApoE –/– mice resulted in significantly decreased circulating BH4 levels, increased atherosclerosis burden and increased plaque macrophage content. Gch1 fl/fl Tie2CreApoE –/– mice showed hallmarks of endothelial cell dysfunction, with increased aortic VCAM-1 expression and decreased endothelial cell dependent vasodilation. Furthermore, loss of BH4 from pro-inflammatory macrophages resulted in increased foam cell formation and altered cellular redox signalling, with decreased expression of antioxidant genes and increased reactive oxygen species. Bone marrow chimeras revealed that loss of Gch1 in both endothelial cells and leucocytes is required to accelerate atherosclerosis. Conclusion: Both endothelial cell and macrophage BH4 play important roles in the regulation of NOS function and cellular redox signalling in atherosclerosis.